Exploring the Streptococci Variants in Children’s Oral Cavity, Its Microbiome Diversity - Juniati Binti Lukman; Zaraswati Dwyana; Mochammad Hatta; Cyril B. Romero (The Indonesian Institute of Science and Technology Research, 2023)
This study aimed to identify the variants of the Streptococcus genus in the oral cavity of healthy individuals. Streptococcus is one of the normal flora, which is part of the lactic acid bacteria (LAB) in the oral cavity. LAB has the ability to produce antimicrobial agents, regulate the host's immune response, and inhibit the growth of pathogenic bacteria. The presence of LAB in the oral cavity is crucial in maintaining oral health and preventing periodontal diseases. This study used observational cross-sectional design with 40 healthy elementary school children as subjects. Swabs were taken from their oral cavities and sent to the laboratory for PCR and sequencing tests. The results revealed that isolates 3S, 4S, 9S, 10S, 14S, and 15S were identified as Streptococcus dysgalactiae, while isolates 1S, 8S, and 9S were identified as Streptococcus mitis. Additionally, isolates 2S, 5S, 7S, 11S, 12S, and 13S were identified as Streptococcus salivarius, isolate 6S was identified as Streptococcus agalactiae, and isolate 17S was identified as Streptococcus oralis. These findings provide valuable information on the identification of oral microbiota, particularly Streptococcus genus variants, which can potentially serve as an alternative therapy for periodontal diseases.